Non-coding RNAs to regulate cardiomyocyte proliferation: A new trend in therapeutic cardiac regeneration - Qin, Kele; Xie, Xiaohui; Tang, Weijie; Yang, Danni; Peng, Jun; Guo, Jianjun; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases remain the leading cause of death worldwide, particularly ischemic heart disease (IHD). It is also classified as incurable given the irreversible damage it causes to cardiomyocytes. Thus, myocardial tissue rejuvenation following ischemia is one of the global primary research concerns for scientists. Interestingly, the mammalian heart thrives after an injury during the embryonic or neonatal period; however, this ability disappears with increasing age. Previous studies have found that specific non-coding (nc) RNAs play a pivotal role in this process. Hence, the review herein summarizes the research on cardiomyocyte regenerative medicine in recent years and sets forth the biological functions and mechanisms of the micro (mi)RNA, long non-coding (lnc)RNA, and circular (circ)RNA in the posttranscriptional regulation of cardiomyocytes. In addition, this review summarizes the roles of ncRNAs in specific species while enumerating potential therapeutic strategies for myocardial infarction.